(untitled) (Journal of Oriental Studies, 2016)
Many scholars suggested that the development of society 21ST century would be accelerated. The interest of the women in labor market policy, their seeking of more independence and doing business can confi rm that assumption. Now days the Japanese women leave their old place in their family and appear on public stage as an independent force of global civilization. In this article, the author has considered the image of Japanese woman in modern society and family.